Randomized, Double-Masked, Sham-Controlled Trial of Ranibizumab for Neovascular Age-Related Macular Degeneration: PIER Study Year 2 - Abraham, Prema; Yue, Huibin; Wilson, Laura (American journal of ophthalmology, 2010)
To evaluate efficacy and safety of quarterly (and then monthly) ranibizumab during the 2-year Phase IIIb, multicenter, randomized, double-masked, sham injection–controlled study of the efficacy and safety of ranibizumab in subjects with subfoveal CNV with or without classic CNV secondary to AMD (PIER) study. Phase IIIb, multicenter, randomized, double-masked, sham injection–controlled trial in patients with choroidal neovascularization (CNV) secondary to age-related macular degeneration (AMD). Patients were randomized 1:1:1 to sham injection (n = 63) or 0.3 mg (n = 60) or 0.5 mg (n = 61) intravitreal ranibizumab monthly for 3 months and then quarterly. During study year 2, eligible sham-group patients crossed over to 0.5 mg ranibizumab quarterly. Later in year 2, all eligible randomized patients rolled over to 0.5 mg ranibizumab monthly. Key efficacy and safety outcomes of the 2-year trial are reported. At month 24, visual acuity (VA) had decreased an average of 21.4, 2.2, and 2.3 letters from baseline in the sham, 0.3 mg, and 0.5 mg groups ( P < .0001 for each ranibizumab group vs sham). VA of sham patients who crossed over (and subsequently rolled over) to ranibizumab decreased across time, with an average loss of 3.5 letters 10 months after crossover. VA of 0.3 mg and 0.5 mg group patients who rolled over to monthly ranibizumab increased for an average gain of 2.2 and 4.1 letters, respectively, 4 months after rollover. The ocular safety profile of ranibizumab was favorable and consistent with previous reports. Ranibizumab provided significant VA benefit in patients with AMD-related CNV compared with sham injection. Ranibizumab appeared to provide additional VA benefit to treated patients who rolled over to monthly dosing, but not to patients who began receiving ranibizumab after >14 months of sham injections.